Analysis of lingual articulation using electropalatography and electromagnetic articulography - Fitzpatrick, Liam (Trinity College (Dublin, Ireland). Centre for Language and Communication Studies, 2001)
Electromagnetic mid-sagittal articulography (EMA) and electropalatography (EPG) are two techniques for measuring lingual activity during speech production. EMA measures the location of a small number of sensors attached to the midline tongue, and EPG detects contact between the tongue and sensors embedded in an artificial palate which fits over the hard palate. Data from each device holds more information then analytical techniques in general use are capable of extracting. They also provide complementary information. Simultaneous use of the techniques would provide more information than either used alone could. This thesis, through the development of tools and analytical techniques, addresses the better exploitation of EPG and EMA data, and investigates their simultaneous use. The techniques are used to addresses some basic issues in phonetic theory by undertaking two exploratory analytical studies.
Keywords: Linguistics, Ph.D.; Ph.D. Trinity College Dublin